2014
DOI: 10.3390/molecules19010767
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase Inhibitory, Antioxidant and Phytochemical Properties of Selected Medicinal Plants of the Lamiaceae Family

Abstract: Abstract:The present study aimed to evaluate acetylcholinesterase (AChE) inhibitory and antioxidant activities of Lamiaceae medicinal plants growing wild in Croatia. Using Ellman's colorimetric assay all tested ethanolic extracts and their hydroxycinnamic acid constituents demonstrated in vitro AChE inhibitory properties in a dose dependent manner. The extracts of Mentha x piperita, M. longifolia, Salvia officinalis, Satureja montana, Teucrium arduini, T. chamaedrys, T. montanum, T. polium and Thymus vulgaris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
125
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(146 citation statements)
references
References 53 publications
16
125
4
1
Order By: Relevance
“…Mints exhibited moderate AChE inhibitory activity, which is consistent with previously reported values (12.5-95%) at different concentrations using different extraction methods and solvents (Oinonen, Jokela, Hatakka, & Vuorela, 2006;Vladimir-Knežević et al, 2014). We found that M. pulegium possessed a moderate AChE inhibitory activity in contrast to Oinonen Table 1 for the full taxa names for sample identification.…”
Section: Ache and Buche Inhibition Activities Of Mintssupporting
confidence: 93%
See 1 more Smart Citation
“…Mints exhibited moderate AChE inhibitory activity, which is consistent with previously reported values (12.5-95%) at different concentrations using different extraction methods and solvents (Oinonen, Jokela, Hatakka, & Vuorela, 2006;Vladimir-Knežević et al, 2014). We found that M. pulegium possessed a moderate AChE inhibitory activity in contrast to Oinonen Table 1 for the full taxa names for sample identification.…”
Section: Ache and Buche Inhibition Activities Of Mintssupporting
confidence: 93%
“…Treatment of AD is limited to symptomatic and palliative medications and, despite enormous effort aimed at understanding the aetiology and pathogenesis of the disease (Vladimir-Knežević et al, 2014), no pharmacotherapeutics have so far been able to stop the progression of AD (Korolev, 2014). Furthermore, adverse reactions to current drugs are frequently more serious than the disease…”
Section: Introductionmentioning
confidence: 99%
“…Based on literature data, donepezil was tested at a 3.0 lM dose, which caused an anti-proliferative activity of about 30% in the SH-SY5Y cell line (Arias, Gallego-Sandín, Villarroya, García, & López, 2005). Our results seemed to confirm data from recent studies, aimed at characterizing the anti-AChE activity of ethanol extracts from 26 medicinal plants belonging to the same Lamiaceae family as sage (Vladimir-Knežević et al, 2014). The inhibiting properties of Salvia officinalis were previously reported in in vitro and in vivo studies.…”
Section: Antioxidant Activity Of Soa541 Fractionsupporting
confidence: 92%
“…In the study of Szwajgier [61] the anti-cholinesterase activity of several phenolic compounds was tested and carnosic acid possessed the highest inhibitory activity, followed by rosmarinic and caffeic acid. In another study, rosmarinic acid showed almost 50% inhibition of AChE in the concentration of 0.25 mg/mL and caffeic acid was almost, equally effective in the high concentrations but in low concentration its inhibitory activity was far below 50% [62].…”
Section: Discussionmentioning
confidence: 97%